Perlindungan Hukum Bagi Kreditur Penerima Fidusia Pasca Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 - Nurcahyanti, Indri Ike; Sukarmi, Sukarmi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the legal principles in executing material guarantees and legal protection for fiduciary creditors to repay their receivables after issuing Constitutional Court Number 18/PUU-XVII/2019. This study used a statutory, conceptual, and case approach with a normative juridical type of research. The results of this study indicated that the legal principles in executing material guarantees after the decision of the Constitutional Court Number 18/PUU-XVII/2019 had changed regarding the executorial title, which was initially in the Grosse deed, into a guarantee certificate. According to the Constitutional Court, norms change did not provide justice, so the executorial title on the fiduciary guarantee certificate did not apply. Legal protection for fiduciary creditors to obtain repayment of their receivables after the decision of the Constitutional Court did not have legal certainty for interested parties.